Zmiany składników bilansu wód w zlewni górniczej = Changes of water budget components in mining drainage area - Polak, Krzysztof; Klich, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Majorities of open-pits are reclaimed as water reservoirs. Such process has great effect on a water environment in scale of drainage area. Those changes can be beneficial not only in comparison with mining condition but also in comparison with natural water condition taking place before mining activity. Open pit mining is giving great opportunity for growing coefficient of surface water storage.
Keywords: wody podziemne; wody powierzchniowe; bilans wód; odwanianie kopalń; zatapianie wyrobisk odkrywkowych; groundwaters; surface water; drainage area; mine dewatering; mine flooding